PROCESSORS: the impacto of graphene - Nascimento, Mario Luis; Filho , João de Lucca (Revista Interface Tecnológica, 2020)
This article investigates and establishes the benefits that graphene has for creating new microprocessors and memory systems. Graphene is a 2D crystalline structure in carbon, very resistant with applications in microelectronics and signal transport. The article demonstrates graphene as an alternative for building new generations of processors with a high speed increase. Finally, the availability of the graphene material and the advantages for the microelectronics area are also presented.